Development of Ethno-STEM Integrated Digital Teaching Material of Heat Concept to Promote Students’ Learning and Innovation Skills - Hafiz Almahfuz Agusti; Asrizal; Rose Amnah; Hidayati; Helma (Postgraduate, University of Mataram, 2024)
Twenty-first century learning requires students to have student’ learning and innovation skills. However, in fact, students' learning and innovation skills are still low. The solution to this problem is the development of ethno-STEM integrated digital teaching material of heat concept to promote students' learning and innovation skills. The aims of this study were to determine the needs analysis, validity, and practicality of the use of ethno-STEM integrated digital teaching materials. The type of research is research and development (R&D) using the Hannafin and Peck model. The research instruments used include needs analysis, validity, and practicality instruments. Data analysis techniques using descriptive statistical analysis. Based on the data analysis, there were three research results. First, the needs analysis showed that students' critical and creative thinking skills were categorized as less with values of 54.36 and 52.92, respectively. Second, the product validity test obtained a value of 91.44 in the excellent category. Third, the product practicality test obtained a value of 82.29 in the excellent category. These results indicate that students' learning and innovation skills can be improved through digital teaching materials. Therefore, the ethno-STEM integrated digital teaching materials are valid and practical for use in learning.